(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Nutrition is a key factor in human life and the development of civilization. The production of sufficient food requires the use of: efficient agricultural techniques, suitable soils and the use of nitrogen (N) fertilizers. However, the use of synthetic nitrogen fertilisers is associated with significant problems, caused by the fact that they are not sufficiently retained in soils to be taken up by plants and a significant proportion of the applied fixed nitrogen is lost. This is a serious economic problem for the farmers and a serious environmental problem for the society. In this work, the known methods for reducing the loss of bound nitrogen when fertilizer formulations are applied to the soil are discussed, and a promising preparation is presented, which is a complex of urea with magnesium sulfate, named magnesium sulfate hexaureate hemi hydrate, [Mg ((H2N)2CO)6] SO41/2 H2O, which can find application both alone and in the formulation of the complex fertilizer formulations, as well as a convenient method for its preparation. The use of [Mg ((H2N)2CO)6] SO41/2 H2O, instead of conventional nitrogen fertilisers, besides the reduction of losses of fixed nitrogen, is that it supplies the soil with the trace elements Mg and S. The low hygroscopicity and the good stability of the preparation are also essential. The known ureate complexes of magnesium sulphate and their preparation are discussed. The proposed new method of solid-phase synthesis, has certain advantages. The use of solid synthesis state methods has a number of advantages: solvent-free synthesis, low-temperature operation, high yields, and the absence of by-products make these methods the most environmentally acceptable.